Combustion Characteristic of a Diesel Engine Operating with Methanol as Alternative Fuel - Akasyah, M Khathri; R., Mamat; Amir, Aziz; Azri, Alias; Nik Rosli, Abdullah (Trans Tech Publications Inc., 2014)
Modelling the compression ignition engine mostly depends on fuel characteristics. The proses involve a model of the real system and carry out experiment as a mean of comparison to understand the behaviour of the system. The diesel engine nowadays operated with different kind of alternative fuels such as natural gas and biofuel. The aim of this article is to study the combustion characteristic occurred in an engine cylinder of a diesel engine when using biofuel. The one-dimensional numerical analysis using GT-Power software is used to simulate the diesel engine. The engine operated at full engine load and difference speed. The methanol fuel used in the simulation is derived from the conventional methanol fuel properties. The analysis of simulations includes the cylinder pressure, combustion temperature and rate of heat release. The simulation result shows that in-cylinder pressure for methanol is slightly higher than diesel fuel in any speed of the engine. It also found that the combustion characteristic on methanol temperature is higher at all crank angle degree of diesel fuel. Mass fraction burns of methanol are much lower than diesel fuel, but burns faster than diesel fuel.